Adsorption of Copper on Transcarpathian Mordenite - V.O. Vasylechko; L.O. Lebedynets; G.V. Gryshchouk; Yu.B. Kuz'ma; L.O. Vasylechko; T.M. Bernats'ka (Adsorption Science & Technology)
The adsorption properties of Ukrainian Transcarpathian mordenite in aqueous copper(II) solutions under dynamic conditions have been investigated. Under optimum conditions (pH of Cu 2+ solution = 6.5; adsorbent thermallly modified over 2.5 h at 150°C; rate of passage of Cu 2+ solution through adsorbent = 3 ml/min) the adsorption capacity of the mordenite towards copper amounted to 1020 μg/g. Copper is effectively desorbed by an aqueous solution of HNO 3 (1:2). Under optimum desorption conditions the effective extraction of copper was 99.8%.